Priority Setting in Damage Control Surgery for Multiple Abdominal Trauma Following Resuscitative Endovascular Balloon Occlusion of the Aorta - Yoonjung Heo; Seok Won Lee; Dong Hun Kim (Journal of Trauma and Injury)
Damage control surgery (DCS) is an abbreviated laparotomy procedure that focuses on controlling bleeding to limit the surgical insult. It has become the primary treatment modality for patients with exsanguinating truncal trauma. Herein, we present the case of a 47-year-old woman with liver, kidney, and superior mesenteric vein (SMV) injuries caused by a motor vehicle collision. The patient underwent DCS following resuscitative endovascular balloon occlusion of the aorta (REBOA). In this case report, we discuss the importance of priority setting in DCS for the treatment of multisystem damage of several abdominal organs, particularly when the patient has incurred a combination of major vascular injuries. We also discuss the implications of damage control of the SMV, perihepatic packing, and right-sided medial visceral rotation. Further understanding of DCS, along with REBOA as a novel resuscitation strategy, can facilitate the conversion of uniformly lethal abdominal injuries into rescuable injuries.